2002
DOI: 10.1007/s00467-001-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis B virus-associated nephropathy in black children

Abstract: The efficacy of interferon (IFN) in the treatment of hepatitis B virus (HBV)-associated nephropathy in black children has not been established. Twenty-four black children with biopsy-proven HBV-associated nephropathy were recruited into the study during the period April 1997 to June 1999. Five defaulted treatment and were excluded from the primary analysis. IFNalpha 2b was administered for 16 weeks. Response to treatment was defined as loss of HBeAg, decrease in proteinuria, and prevention of deterioration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…None of the 9 patients who did not clear HBeAg showed remission of proteinuria, while 2 developed progressive renal failure. In the control group, only 5% of the patients showed spontaneous clearance of HBeAg, and none had remission of proteinuria [41]. These studies support the notion that antiviral therapy is effective in inducing proteinuria remission and preserving renal function in patients with HBV-associated MN.…”
Section: Treatmentsupporting
confidence: 69%
See 1 more Smart Citation
“…None of the 9 patients who did not clear HBeAg showed remission of proteinuria, while 2 developed progressive renal failure. In the control group, only 5% of the patients showed spontaneous clearance of HBeAg, and none had remission of proteinuria [41]. These studies support the notion that antiviral therapy is effective in inducing proteinuria remission and preserving renal function in patients with HBV-associated MN.…”
Section: Treatmentsupporting
confidence: 69%
“…In contrast, none of the patients treated conservatively underwent seroconversion. On the other hand, in the only study to report on the effect of interferon-α 2 b in 24 African children with HBV-associated MN, 10 of the children who completed 16 weeks of therapy (52.6%) responded with clearance of HBeAg by 40 weeks [41]. None cleared HBsAg.…”
Section: Treatmentmentioning
confidence: 99%
“…A low incidence of HBV was found in this study, unlike in Durban with a high prevalence of HBV nephropathy [16,17]. Although HIV screening was not performed in any of the patients, mainly due to financial reasons, previous reports from South Africa showed that HIV-associated nephropathy is uncommon in children, because of their demise before they develop nephropathy as adults [5].…”
Section: Discussionmentioning
confidence: 98%
“…Disease remission is especially evident after HBeAg seroconversion. A significant percent of adults (30%) may progress to renal failure and as many as 10% will require maintenance dialysis (Bhimma et al, 2002).…”
Section: Hbv-related Glomerulonephritismentioning
confidence: 99%